PENGARUH SUHU DAN EKSTRAK BIJI NIMBA (Azadirachta indica A. Juss) TERHADAP JUMLAH HEMOSIT JENGKERIK (Gryllus mitratus Burm.) - Hikmat Kasmara; Ahmad Ridwan; Darmadi Goenarso (Universitas Padjadjaran, 2002)
A B S T R A C T The effect of temperature and neem seed extract (Azadirachta indica A. Juss) on the haemocyte number of cricket (Gryllus mitratus Burm.) has been studied. Temperatures applied in this experiment were 25o ± 1o C, 30o ± 1o C and 35o ± 1o C. Neem seed extract was injected in volumes of 10 ml/g body weight into the ventral abdomen intersegment between segment 5 and 6 of the insect body. The concentrations of neem seed extract were 0.0 %, 2.5 %, 5.0 %, 10.0 % and 20.0 %. Controls without injection were also analysed. Hemolymph was taken by sterile needle from the prothorax. The experiment design was randomized block design (RBD) factorial pattern. In this experiment, four types of haemocyte were observed e.g. prohaemocyte (PR), plasmatocyte (PL), coagulocyte (CO) and granulocyte (GR). At 25o C, treatment of 0.0 %, 2.5 % and 5.0 % neem’s seed extract to increased the haemocyte number during 3 hours exposure, at 10.0 % neem seed extract the haemocyte number started to decrease, while at 20.0 % the haemocyte number returned to the same level as the control. The same pattern was obtained for the treatment at 30o and 35o C. When the exposure was increased to 24 hours, at 25o C, application of neem seed extract 0.0 %, 2.5 %, 5.0 %, 10.0 % and 20.0 % increased haemocyte number compared to control. The differences of the haemocyte number between control and treatment at 30o C, only occurred on the 5.0 % neem seed extract. At 35o C, the haemocyte number of the 0.0 %, 2.5 % and 5.0 % neem seed extract were equal to control, while on the 10.0 % and 20.0 %, the haemocyte number were lower than control. The lowest haemocyte number was obtained at 35o C, 20.0 % neem seed extract and 24 hours exposure. Key words : temperature, neem seed extract, haemocyte, cricket